A Culturally Contingent Resource: How National Context Moderates the Link between Home Book Collections and Academic Achievement - Liu, Yunbing; Wen, Mingqi (Journal of Humanities and Social Sciences Studies, 2025)
Academic achievement is a key indicator of individual development and national prosperity. Although the positive impact of home resources on academic achievement has been confirmed by existing research, its underlying psychological mechanisms (e.g., through curiosity) and the moderating effects of macro-level sociocultural contexts remain underexplored. This study addresses these gaps using PISA 2022 data from 582,810 students across 67 countries/economies. We investigated the mediating role of student curiosity in the relationship between home book collections, and examined whether this pathway is moderated by a key national-level factor: the proportion of the Muslim population. Multilevel Structural Equation Modeling (MSEM) revealed that home book collections positively predicted academic achievement, a relationship that was partially mediated by student curiosity. Crucially, the positive effect of home book collections on achievement was significantly stronger in countries with a lower proportion of Muslim population. These findings highlight the cultural contingency of educational inputs. The weaker association in societies with a higher proportion of Muslims suggests that non-material knowledge transmission pathways, such as oral traditions and communal learning, may be more salient for intellectual development in these contexts. This underscores the need for culturally calibrated educational policies. While resource-provision programs may be effective in some nations, interventions designed to leverage indigenous learning structures may prove more impactful in others